Multi-Criteria Optimization of a Biomass-Based Hydrogen Production System Integrated With Organic Rankine Cycle - Zhang, Xiaoqi; Zhou, Yuling; Jia, Xiaotong; Feng, Yuheng; Dang, Qi (Frontiers in Energy Research, 2020)
Biomass-based gasification is an attractive and promising pathway for hydrogen production. In this work, a biomass-based hydrogen production system integrated with organic Rankine cycle was designed and investigated to predict the performance of hydrogen production yield and electricity generation under various operating conditions. The modified equilibrium model presented desirable results for the produced syngas compositions compared with the experimental data. Hydrogen yields from four types of biomass (wood chips, daily manure, sorghum and grapevine pruning wastes) were compared under the same operating condition, with woodchips exhibiting the maximum hydrogen yield of 11.59 (mol/kg). The effects of gasification temperature, equivalence ratio and steam-to-biomass ratio on the hydrogen yield and electricity generation were investigated by the response surface method. Furthermore, the system was optimized using genetic algorithm based on the response surface model. A preferred optimal solution with the hydrogen yield of 39.31 (mol/kg) and output power of 3558.08 (kW) was selected by the LINMAP method.